Investigations of the electrochemical behaviour of room temperature ionic liquids - Burgess, Ian (2015)
The existence of Room Temperature Ionic Liquids (RTILs) has been known for a long time, but only recently have they been pulled to the forefront of chemical research. This increase in attention can be attributed to a keen interest in their intrinsic properties for a wide variety of potential applications. RTILs have been used as alternative solvents for organic synthesis as well as catalysis, as well as supports for the purification or extraction of metals. Being ionic in nature and liquid at temperatures below 100°C, RTILs lend themselves to the electrochemist. As a result, they have been looked at for use in electrochemical systems such as high capacity batteries and supercapacitors. Due to their extremely high density of charge carriers relative to more well-known aqueous electrochemical systems, a new theoretical approach must be taken. Currently, a large gap exists between theoretical approaches and experimental results. The work contained within this thesis aims to provide insight into the interface between a RTIL and an electrified gold electrode.